On a matching distance between rooted phylogenetic trees - Bogdanowicz, Damian; Giaro, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
The Robinson?Foulds (RF) distance is the most popular method of evaluating the dissimilarity between phylogenetic trees. In this paper, we define and explore in detail properties of the Matching Cluster (MC) distance, which can be regarded as a refinement of the RF metric for rooted trees. Similarly to RF, MC operates on clusters of compared trees, but the distance evaluation is more complex.
Keywords: phylogenetic tree; phylogenetic tree metric; phylogenetic tree comparison; matching cluster distance; matching split distance